High Abundances of Species in Protected Areas in Parts of their Geographic Distributions Colonized during a Recent Period of Climatic Change. Issue 2 (26th September 2014) - Gillingham, Phillipa K.; Alison, Jamie; Roy, David B.; Fox, Richard; Thomas, Chris D.
Abstract: It is uncertain whether Protected Areas (PAs) will conserve high abundances of species as their distributions and abundances shift in response to climate change. We analyzed large datasets for 57 butterfly and 42 odonate species (including four that have recently colonized Britain). We found that 73 of 94 species with sufficient data for analysis were more abundant inside than outside PAs in the historical parts of their British distributions, showing that PAs have retained high conservation value. A significant majority (61 of 99 species) was also more abundant inside PAs in regions they have colonized during the last 30–40 years of climate warming. Species with relatively high abundances inside PAs in long‐established parts of their distributions were also disproportionately associated with PAs in recently colonized regions, revealing a set of relatively PA‐reliant species. Pas, therefore, play a vital role in the conservation of biodiversity as species' ranges become more dynamic.